2005
DOI: 10.1002/jcb.20720
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular proteolytic activity of cathepsin B is associated with capillary‐like tube formation by endothelial cells in vitro

Abstract: The lysosomal cysteine protease cathepsin B is implicated in degradation of extracellular matrix (ECM), a crucial step in a variety of physiological and pathological processes, including tumor dissemination and angiogenesis. In this study, we analyzed the contribution of extracellular and intracellular cathepsin B activity on the formation of capillary-like tubular structures by human umbilical vein endothelial cells (HUVECs) grown on Matrigel matrix, using general and specific cysteine protease inhibitors. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Treatment of cells with membrane-permeable CA-074Me effectively abolished intracellular CB activity, which is implicated in the degradation of ECM. 48 CA-074Me conferred a protective effect in OA-induced cell apoptosis and reduced amyloid precursor protein accumulation and a-spectrin cleavage in Alzheimer's disease. 49 In previous study, specific CB inhibitor CA-074Me attenuated the expression of CB in the development of ischemic astrocytic cell death both in in vivo and in vitro ischemic models.…”
Section: Discussionmentioning
confidence: 93%
“…Treatment of cells with membrane-permeable CA-074Me effectively abolished intracellular CB activity, which is implicated in the degradation of ECM. 48 CA-074Me conferred a protective effect in OA-induced cell apoptosis and reduced amyloid precursor protein accumulation and a-spectrin cleavage in Alzheimer's disease. 49 In previous study, specific CB inhibitor CA-074Me attenuated the expression of CB in the development of ischemic astrocytic cell death both in in vivo and in vitro ischemic models.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, researchers have proposed that cathepsin B plays critical roles in the invasion and metastasis of cancers (16)(17)(18). Research demonstrated that the expression and activity of these enzymes are related to cancer stage and metastasis and that these enzymes may be used as predictors (7).…”
mentioning
confidence: 99%
“…Uncleaved cresyl violet substrates show an emission peak at 570 nm when excited at 540 nm, and cleaved cresyl violet has an emission peak at 628 nm when excited at 540 nm ( Figure 5) (Boonacker et al 2003a). The activity can be imaged using confocal laser scanning microscopy (Boonacker et al 2002(Boonacker et al ,2003aPremzl et al 2006) and measured per individual cell using flow cytometry (Creasy et al 2007). In the latter study, activity of cathepsin B, L, and S was combined with immunofluorescence staining of leukocytes to detect cell lineage-specific activity in heterogeneous cell populations (Creasy et al 2007).…”
Section: Magic Red Substrates the Cresyl Violet-based Magicmentioning
confidence: 99%